PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI, LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT BPR KITA CENTRADANA KUTA BADUNG - Apriyana, A.A Ngurah Nanda; Riana, I Gede (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of transformational leadership, communication and work environment on employee job satisfaction. This research was conducted at PT. BPR We Centradana Kuta, Badung. The number of samples taken 90 people with sampling methods saturated. Data collected through interviews and questionnaires. The analysis technique used is multiple linear regression. Based on the analysis (1) of transformational leadership is partially significant positive effect on job satisfaction of employees, (2) communication in partial significant positive effect on job satisfaction of employees, (3) the work environment is partially significant positive effect on employee satisfaction. Limitations of this study where researchers only use three variables to measure job satisfaction. Further research should further refine this research by adding other variables related to job satisfaction.
Keywords: kepemimpinan transformasional; komunikasi; lingkungan kerja; kepuasan kerja